Pengaruh Perbandingan Dosis Mikoriza Arbus Kula Terhadap Pertumbuhan Bibit Jati Putih (Gmelina sp.) - Ignatius Asa; Mamie E. Pellondo’u; Norman P. L. B. Riwu Kaho; Wilhelmina Seran (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2023)
White teak, which has the scientific name Gmelina arborea, is a productive wood-producing tree. White Teak (Gmelina sp.) is a wood-producing tree which has a yellowish-white color with fine fibrous and gray skin. The use of this wood is for construction materials, furniture, pulp, floor raises, carpentry tools and so on. Mycorrhiza is a group of soil fungi whose life prefers to cooperate with plant or tree roots, so that these fungi get a supply of liquid sugar from plants and vice versa these fungi exchange it in the form of water and nutrients needed for plant growth. This study aims to determine the effect of optimal mycorrhizal doses on the growth of white teak seedlings. This study used a completely randomized design (CRD) analysis with Ducan's Ducan Multiple Reange Post Test. Observations were made on the increase in seedling height, increase in stem diameter and number of leaves. The results showed that the treatment of the growing media had no effect because the doses given were insufficient.